Design of Inventory System at Putri Gemilang Crackers Factory Using End-User Development Method - Dela Nabila Apriyani; Surya Ade Saputera (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to design a web-based inventory information system at Pabrik Kerupuk Putri Gemilang using the End-User Development (EUD) method. The problems found in the inventory management process were that it was still carried out manually using notebooks, causing recording errors, delays in report preparation, and discrepancies between stock records and physical stock in the warehouse. The research method used was a qualitative method with data collection techniques through observation and interviews. The End-User Development approach was applied because it involves users directly in the process of system requirement analysis and system design, so the resulting system is more suitable for operational needs. The results of the study indicate that the web-based inventory system is able to assist the management of item data, incoming goods, outgoing goods, and inventory reports more effectively and efficiently. The system is also able to display real-time stock information and generate automatic reports to support monitoring and decision-making processes. In addition, the system was designed with a simple and user-friendly interface to make it easier for users to operate the system. The implementation of this web-based inventory information system is expected to improve the effectiveness, accuracy, and integration of inventory management at Pabrik Kerupuk Putri Gemilang.